Um discurso afinado: o episcopado católico frente à “política” e ao “social” - Seidl, Ernesto (2007)
This article analyses the relations of Brazil’s Catholic bishops and their position, while a representation group, regarding “political” and “social” issues. The purpose of the study is twofold: it tries to cast light on the logic of the mechanisms which mold the representations of the Brazilian high clergy as a homogeneous group responsible for elaborating univocal messages to a heterogeneous public; and it tries to apprehend a vast set of strategies of making and presenting official well-adapted discourses to both Brazil’s and the world’s realities, as a way of legitimating the Church as an authority on a vast sort of subjects.